Utilization Of Restorative Justice In The Handling Of Child Crimes From The Perspective Of Utilities Theory - Ansori Lubis, Muhammad (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
In essence, everyone who commits a crime will face legal consequences, even minors. Although restorative justice policies and procedures for juvenile offenders have been developed, they have not yet been fully put into practice. The truth is that not all police detectives at the regional sector level comprehend how to use restorative justice to resolve juvenile criminal cases. The purpose of this study is to comprehend and evaluate the paradigm of restorative justice for juvenile offenders from a utility theory standpoint. The difficulties in applying restorative justice to juvenile offenders at the police level are also examined in this study. This study is a normative, legal, descriptive, and analytical study. Secondary data were used in this study, and they were gathered by employing library research techniques. A qualitative method is used in data analysis. The study's findings demonstrate that applying restorative justice to kids who break the law is essentially protecting kids from the law itself, with the goal that kids will still be protected even when mistakes are made. The use of restorative justice is a type of legal benefit from the standpoint of legal advantages. The community benefits from the law that has been created by the government, including both those who are criminals and those who are among their victims. In other words, the law is not only created to punish, but also to protect, advance the law, and benefit society. Second, that barriers to the use of restorative justice can be divided into two categories: internal barriers arising from the juvenile offenders and external barriers in the form of community environmental barriers, family barriers, juvenile officer barriers, and juvenile mediator barriers.